Predictors and moderators of COVID-19 pandemic fatigue in Hong Kong. Issue 5 (May 2023) - Lai, Daniel W.L.; Jin, Jiahui; Yan, Elsie; Lee, Vincent W.P.
Abstract: Background: Anti-pandemic fatigue has inevitably set in owing to the high intensity and prolonged presence of pandemic preventive measures. Globally, COVID-19 remains severe; however, pandemic fatigue may lead to less efficient viral control. Methods: A total of 803 participants residing in Hong Kong interviewed via telephone using a structured questionnaire. Linear regression was employed to test the corelates of anti-pandemic fatigue and the moderators that could potentially impact the appearance of fatigue. Results: When confounding effects of demographic factors (e.g., age, gender, educational attainment, and economic activity status) were avoided, daily hassles were found to be a core factor associated with anti-pandemic fatigue (B =0.369, SE =0.049, p = 0.000). For people with a higher level of pandemic-related knowledge and fewer obstacles brought about by preventive measures, the impact of daily hassles on pandemic fatigue weakened. Moreover, when pandemic-related knowledge was high, there was no positive association between adherence and fatigue. Conclusions: This study confirms that daily hassles can lead to anti-pandemic fatigue, which can be mitigated by improving the general public's understanding of the virus and developing more convenient measures.